2020
DOI: 10.3390/genes11080949
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing of SARS-CoV-2: Adapting Illumina Protocols for Quick and Accurate Outbreak Investigation during a Pandemic

Abstract: The COVID-19 pandemic has spread very fast around the world. A few days after the first detected case in South Africa, an infection started in a large hospital outbreak in Durban, KwaZulu-Natal (KZN). Phylogenetic analysis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) genomes can be used to trace the path of transmission within a hospital. It can also identify the source of the outbreak and provide lessons to improve infection prevention and control strategies. This manuscript outlines the ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 26 publications
(27 reference statements)
0
61
0
1
Order By: Relevance
“…A multiplex amplicon-based approaches by CDC 23 where the effectively generating full length genome sequences <Ct of 33 although Ct. values between 30 and 33, genome recovery varied between samples. In another report, ARTIC primers were used initially for amplification of SAR-COV-2 clinical samples and the full-length genome recovery from sequencing these amplicons were compared by different library preparation methods for Illumina sequencing [32]. They reported that samples below Ct. <27 produced near full-length genomes, although from samples with Ct. <30, longer and higher quality genomes were reported.…”
Section: Discussionmentioning
confidence: 99%
“…A multiplex amplicon-based approaches by CDC 23 where the effectively generating full length genome sequences <Ct of 33 although Ct. values between 30 and 33, genome recovery varied between samples. In another report, ARTIC primers were used initially for amplification of SAR-COV-2 clinical samples and the full-length genome recovery from sequencing these amplicons were compared by different library preparation methods for Illumina sequencing [32]. They reported that samples below Ct. <27 produced near full-length genomes, although from samples with Ct. <30, longer and higher quality genomes were reported.…”
Section: Discussionmentioning
confidence: 99%
“…A multiplex amplicon-based approach by CDC was effective in generating full length genome sequences <Ct of 33 although Ct values between 30 and 33, genome recovery varied between samples [ 38 ]. In another report, ARTIC primers were used initially for amplification of SARS-CoV-2 clinical samples and the full-length genome recovery from sequencing these amplicons were compared by different library preparation methods for Illumina sequencing [ 39 ]. They reported that samples below Ct <27 produced near full-length genomes, although from samples with Ct <30, longer and higher quality genomes were reported.…”
Section: Discussionmentioning
confidence: 99%
“…The number of SARS-CoV-2 genome sequences in the public database is growing rapidly (Shu & McCauley, 2017). The exponential growth of the publicly available SARS-CoV-2 genome sequences is attributable to the rapid genome sequencing, development of data analysis workflow, and data sharing by researchers worldwide (Campos et al, 2020;Pillay et al, 2020;Quick, 2020). Currently, most of the sequencing workflows are created for the use of the Oxford Nanopore and Illumina's sequencing platforms (Colson et al, 2020;Nasir et al, 2020;Resende et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The use of this metatranscriptomics approach for the sequencing of a large number of SARS-CoV-2 samples is therefore limited. After releasing the first SARS-CoV-2 complete genome sequence, extensive efforts have been made to develop various sequence-based next-generation sequencing (NGS) library preparation methods to increase the yield of viral specific sequencing reads (Campos et al, 2020;Pillay et al, 2020;Quick, 2020). PCR amplification and hybridization are two commonly used sequence-based approaches that enable SARS-CoV-2 target enrichment (Xiao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%